Self-lubricating mold guide plate and preparation method thereof
By microwave treatment and nickel plating on scale graphite, the affinity between graphite and metal is improved, and the problem of graphite peeling under large loads is solved, achieving a longer service life and a lower waste rate.
Patent Information
- Application Number
- CN202411951973.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-27
AI Technical Summary
When existing self-lubricating mold guide plates are subjected to large loads, the graphite phase is prone to peel off, resulting in an increase in surface roughness and an increase in product waste rate.
By treating the scale graphite under microwaves of 20KW to 30KW for 5 minutes to 15 minutes, the π bonds are opened, the interlayer spacing is increased, the diffusion of metal atoms is promoted, the affinity between graphite and metal is improved, and the nickel plating treatment is carried out to reduce the friction between graphite and metal powder.
It effectively prevents the peeling of the graphite phase under large loads, improves the interface bonding strength of the material, extends the service life of the product, reduces the scrap rate, and meets the requirements of high-precision molds for the performance of guide plates.
Smart Images

Figure CN119747661A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of industrial product processing and preparation, and particularly relates to a self-lubricating die guide plate and a preparation method thereof. Background Art
[0002] The guide plate in the mold plays a key guiding and positioning role and is a core element in mold manufacturing. In the automotive mold industry, especially in the field of large and medium-sized stamping molds, guide parts are often made of copper alloys such as tin bronze, lead bronze, aluminum bronze, or composited with low-carbon steel with excellent performance, and advanced copper-steel bimetallic composites are produced through powder metallurgy technology. However, due to the huge demand for guide plates in the production of automotive coverings, the average weight of copper alloy consumed by each set of molds is between 20 and 30 kilograms. During use, the guide plates are often subject to wear and impact, resulting in irreparable damage, and eventually become waste, resulting in a waste of resources. The mold guide plates produced with copper-based graphite self-lubricating materials effectively solve these challenges, significantly improve the actual service life of the material, and reduce waste.
[0003] In the existing technical solution, the copper-based graphite self-lubricating die guide plate is directly prepared by powder metallurgy. Although this method can obtain better performance and preliminarily solve the problem of non-wetting, non-reaction and incompatibility between the graphite and copper interface in the material, it is found from the subsequent use process that when it is subjected to a large load, the graphite phase peels off, resulting in a large number of pits on the surface of the self-lubricating die guide plate, resulting in an increase in surface roughness and an increase in the scrap rate of the product. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a self-lubricating die guide plate and a preparation method thereof, which can effectively prevent the peeling of the graphite phase of the self-lubricating die guide plate under a large load.
[0005] In order to achieve the above object, the technical solution of the present invention is as follows.
[0006] A first aspect of the present invention provides a method for preparing a self-lubricating mold guide plate, comprising the following steps:
[0007] The flake graphite is subjected to microwave treatment at 20KW to 30KW for 5min to 15min to open the π bond of the flake graphite, and the microwave-treated flake graphite is placed in a plating solution for nickel plating to obtain nickel-plated flake graphite;
[0008] Nickel-plated flake graphite and metal powder are mixed to obtain mixed powder, the mixed powder is put into a mold for hot pressing and sintering, and a novel self-lubricating mold guide plate is obtained after cooling and demoulding.
[0009] The present invention can open the π bonds of the flake graphite by subjecting the flake graphite to microwave treatment at 20KW to 30KW for 5min to 15min, thereby increasing the spacing between layers, making it easy for metal atoms to diffuse into graphite crystals, improving the affinity between the flake graphite and the metal, and ensuring the interface bonding strength of the material. The flake graphite after the microwave treatment is nickel-plated, which can further improve the lubrication performance of the flake graphite, reduce the friction between the flakes and the metal powder, and further prevent the graphite phase from falling off, thereby improving the service life of the product and reducing the scrap rate.
[0010] More importantly, if the microwave treatment power is lower than 20KW~30KW or the treatment time is shorter than 5min~15min, the π bonds of flake graphite cannot be opened, and it is difficult for metal atoms to diffuse into the graphite crystal. If it is higher than 20KW~30KW or the treatment time is longer than 5min~15min, excessively large pores will be generated, forming intracrystalline pore defects, resulting in increased internal defects in flake graphite and decreased strength.
[0011] In another preferred embodiment, the specific process of the nickel plating treatment is as follows:
[0012] The microwave-treated flake graphite is placed in plating solution A, and then plating solution B is added, reacted at 55° C. to 80° C. for 20 min to 40 min, washed, filtered, and dried to obtain nickel-plated flake graphite;
[0013] In the plating solution A, the mass ratio of NiSO4, Na3C6H5O7, NaH2PO2 and water is 3.5-4:2.5-3.5:2.5-3.5:100;
[0014] In the plating solution B, the mass ratio of NaOH, NH4Cl and water is 0.2-0.5:10-15:100.
[0015] In another preferred embodiment, the mass volume ratio of the flake graphite, the plating solution A and the plating solution B is 1 kg: 5 L ~ 6 L: 5 L ~ 6 L.
[0016] In another preferred embodiment, the particle size of the flake graphite is 200 mesh to 325 mesh.
[0017] In another preferred embodiment, the metal powder is obtained by mixing copper powder, nickel powder and titanium powder in a mass ratio of 80-85:8-10:2-5.
[0018] In another preferred embodiment, the specific process of hot pressing sintering is as follows:
[0019] The mixed powder is heated to 800°C to 900°C at a heating rate of 50°C / min to 100°C / min under a vacuum condition of 20MPa to 30MPa, and kept at this temperature for 0.5h to 1h.
[0020] In another preferred embodiment, the mixing stirring speed is 30 rpm / min to 100 rpm / min, and the mixing time is 5 h to 10 h.
[0021] A second aspect of the present invention provides the self-lubricating die guide plate.
[0022] Compared with the prior art, the present invention has at least the following beneficial effects:
[0023] (1) The present invention controls the time and power of microwave treatment to open the π bond of flake graphite. If the microwave treatment power is too small or the time is too short, the graphite π bond is opened to a small extent, the interlayer spacing cannot be effectively opened, and it is difficult for metal atoms to diffuse into the graphite crystal; if the microwave treatment power is too large or the time is too long, the graphite π bond is opened to a large extent, the interlayer spacing will be excessively opened, forming intracrystalline pore defects, resulting in an increase in internal defects of graphite and a decrease in strength. Therefore, it is necessary to control the power of microwave treatment to 20KW to 30KW and the time to 5min to 15min, so as to achieve the degree of increasing the diffusion of metal atoms into the graphite crystal, enhance the affinity of graphite and metal, ensure the interface bonding strength of the material, and then prevent the occurrence of graphite phase peeling when the self-lubricating mold guide plate is subjected to a large load. In addition, with the cooperation of nickel plating treatment, the friction between graphite and metal powder can be further reduced, further preventing the shedding of graphite phase.
[0024] (2) The present invention introduces Ni and Ti elements by optimizing the metal powder composition. Compared with the existing metal composition of Cu, Ni or Cu, Sn, the present invention introduces Ni and Ti simultaneously on the basis of Cu, which can form Ni3Ti at the structure and interface, further improve the interface bonding strength and mechanical properties, ensure the service performance and service life of the mold guide plate, and make it meet the requirements of future high-precision molds for guide plate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The microstructure and element analysis diagram of the self-lubricating mold guide plate in Example 1 of the present invention; wherein, a is the scanning electron microscope microstructure, b is the EDS energy spectrum surface scanning of the Cu element; c is the EDS energy spectrum surface scanning of the Ni element; d is the EDS energy spectrum surface scanning of the Ti element.
[0026] Figure 2 This is a diagram showing the result after the self-lubricating mold guide plate in Example 1 of the present invention has been impacted. DETAILED DESCRIPTION
[0027] The following will be combined with the specific embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] The methods described in the embodiments of the present invention are conventional methods unless otherwise specified. The materials, reagents, etc. used can be obtained from commercial sources unless otherwise specified.
[0029] In the existing public information, copper-based graphite self-lubricating materials are directly prepared by powder metallurgy. Although this method can obtain better material properties and preliminarily solve the problems of non-wetting, non-reaction and incompatibility between graphite and copper in the material. However, judging from the subsequent on-site feedback and the service performance of the material under actual working conditions, the existing technology still cannot meet the requirements of future high-precision molds for the performance of the guide plate, especially when the material is subjected to a large load, when the graphite phase peels off, a large number of pits will appear on the mold guide plate, resulting in increased surface roughness of the product and an increase in the scrap rate of the product.
[0030] The present invention greatly improves the affinity between graphite and metal through microwave treatment and graphite nickel plating treatment, which advantageously ensures the interface bonding strength of the material, and effectively prevents the occurrence of graphite phase peeling when the self-lubricating mold guide plate is subjected to a large load. In addition, the metal powder composition is further optimized, and Ni and Ti elements are introduced. Compared with the existing metal composition of Cu, Ni or Cu, Sn, the present invention introduces Ni and Ti at the same time on the basis of Cu, which can form Ni3Ti at the interface, further improve the interface bonding strength and mechanical properties, ensure the service performance and service life of the mold guide plate, and make it meet the requirements of future high-precision molds for the performance of the guide plate.
[0031] A self-lubricating die guide plate and its preparation method are described in detail below. The purity of the pure copper powder, pure nickel powder and pure titanium powder in the following examples is 99.9%.
[0032] Example 1
[0033] A method for preparing a self-lubricating mold guide plate comprises the following steps:
[0034] S1. Treat 200-mesh flake graphite with a microwave at 20 KW for 15 min to obtain microwave-treated flake graphite.
[0035] S2, placing the microwave-treated flake graphite in plating solution A and stirring evenly, then pouring into plating solution B and stirring evenly, reacting at 55°C for 20 minutes, then washing, filtering and drying to obtain nickel-plated flake graphite; wherein the mass volume ratio of flake graphite, plating solution A and plating solution B is 1kg:5L:5L;
[0036] In plating solution A, the mass ratio of NiSO4, Na3C6H5O7, NaH2PO2 and water is 3:3.5:3.5:100;
[0037] In plating solution B, the mass ratio of NaOH, NH4Cl and water is 0.2:10:100.
[0038] S3. Pure copper powder, pure nickel powder and pure titanium powder are mixed in a mass ratio of 85:10:5 to obtain metal powder; nickel-plated flake graphite and metal powder are mixed in a mass ratio of 0.2:9.8, and mixed and stirred at 30 rpm / min for 5 hours to obtain mixed powder; the particle size of pure copper powder, pure nickel powder and pure titanium powder are all 200 mesh.
[0039] S4. Hot-press the mixed powder and sinter it. Pump the sintering furnace to vacuum. The hot-pressing temperature is 800°C, the heating rate is 50°C / min, the temperature is kept for 0.5 hours, and the pressure is 20MPa. After cooling and demoulding with the furnace, a self-lubricating mold guide plate is obtained.
[0040] The microstructure of the self-lubricating die guide plate was measured, and the results are as follows: Figure 1 As shown, from Figure 1 It can be seen that the self-lubricating die guide plate has uniform structure and good interface bonding.
[0041] Example 2
[0042] A method for preparing a self-lubricating mold guide plate comprises the following steps:
[0043] S1. The 275-mesh flake graphite was subjected to microwave treatment at 25 KW for 10 min to obtain microwave-treated flake graphite.
[0044] S2, placing the microwave-treated flake graphite in plating solution A and stirring evenly, then pouring into plating solution B and stirring evenly, reacting at 70°C for 30 minutes, then washing, filtering and drying to obtain nickel-plated flake graphite; wherein the mass volume ratio of flake graphite, plating solution A and plating solution B is 1kg:6L:6L;
[0045] In plating solution A, the mass ratio of NiSO4, Na3C6H5O7, NaH2PO2 and water is 4:3.5:2.5:100;
[0046] In each liter of plating solution B, the mass ratio of NaOH, NH4Cl and water is 0.4:12:100.
[0047] S3. Pure copper powder, pure nickel powder and pure titanium powder are mixed in a mass ratio of 85:10:5 to obtain metal powder; nickel-plated flake graphite and metal powder are mixed in a mass ratio of 0.6:9.4, and mixed and stirred at 50 rpm / min for 8 hours to obtain mixed powder; the particle size of pure copper powder, pure nickel powder and pure titanium powder is 275 mesh.
[0048] S4. Hot-press the mixed powder and sinter it. Pump the sintering furnace to vacuum. The hot-pressing temperature is 850°C, the heating rate is 80°C / min, and the mixture is kept warm for 1 hour at a pressure of 25 MPa. After cooling in the furnace, the mixture is demoulded to obtain a self-lubricating mold guide plate.
[0049] Example 3
[0050] A method for preparing a self-lubricating mold guide plate comprises the following steps:
[0051] S1. 325 mesh flake graphite is subjected to microwave treatment at 30 KW for 5 min to obtain microwave-treated flake graphite.
[0052] S2. Place the microwave-treated flake graphite in plating solution A and stir evenly, then pour in plating solution B and stir evenly, and react at 80°C for 40 minutes, then wash, filter and dry to obtain nickel-plated flake graphite; wherein the mass volume ratio of flake graphite, plating solution A and plating solution B is 1kg:6L:5L.
[0053] In plating solution A, the mass ratio of NiSO4, Na3C6H5O7, NaH2PO2 and water is 4:3:3:100;
[0054] In plating solution B, the mass ratio of NaOH, NH4Cl and water is 0.5:15:100.
[0055] S3. Pure copper powder, pure nickel powder and pure titanium powder are mixed in a mass ratio of 85:10:5 to obtain metal powder; nickel-plated flake graphite and metal powder are mixed in a mass ratio of 0.8:10, and the mixture is stirred at 100 rpm / min for 10 hours; the particle size of pure copper powder, pure nickel powder and pure titanium powder is 325 mesh.
[0056] S4. Hot-press the mixed powder and sinter it. Pump the sintering furnace to vacuum. The hot-pressing temperature is 900°C, the heating rate is 100°C / min, and the temperature is kept for 1 hour at a pressure of 30 MPa. After cooling and demoulding with the furnace, a self-lubricating mold guide plate is obtained.
[0057] Comparative Example 1
[0058] A method for preparing a self-lubricating mold guide plate comprises the following steps:
[0059] S1. Treat 200-mesh flake graphite with a microwave at 20 KW for 15 min to obtain microwave-treated flake graphite.
[0060] S2, placing the microwave-treated flake graphite in plating solution A and stirring evenly, then pouring into plating solution B and stirring evenly, reacting at 55°C for 20 minutes, then washing, filtering and drying to obtain nickel-plated flake graphite; wherein the mass volume ratio of flake graphite, plating solution A and plating solution B is 1kg:5L:5L;
[0061] In plating solution A, the mass ratio of NiSO4, Na3C6H5O7, NaH2PO2 and water is 3:3.5:3.5:100;
[0062] In plating solution B, the mass ratio of NaOH, NH4Cl and water is 0.2:10:100.
[0063] S3. Mix nickel-plated flake graphite and pure copper powder in a mass ratio of 0.2:9.8, stir at 30 rpm for 5 hours to obtain a mixed powder; the pure copper powder has a particle size of 200 mesh.
[0064] S4. Hot-press the mixed powder and sinter it. Pump the sintering furnace to vacuum. The hot-pressing temperature is 800°C, the heating rate is 50°C / min, the temperature is kept for 0.5 hours, and the pressure is 20MPa. After cooling and demoulding with the furnace, a self-lubricating mold guide plate is obtained.
[0065] Comparative Example 2
[0066] A method for preparing a self-lubricating mold guide plate comprises the following steps:
[0067] S1. Place 200-mesh flake graphite in plating solution A and stir evenly, then pour into plating solution B and stir evenly, react at 55°C for 20 minutes, then wash, filter and dry to obtain nickel-plated flake graphite; wherein the mass volume ratio of flake graphite, plating solution A and plating solution B is 1kg:5L:5L;
[0068] In plating solution A, the mass ratio of NiSO4, Na3C6H5O7, NaH2PO2 and water is 3:3.5:3.5:100;
[0069] In plating solution B, the mass ratio of NaOH, NH4Cl and water is 0.2:10:100.
[0070] S2. Pure copper powder, pure nickel powder and pure titanium powder are mixed in a mass ratio of 85:10:5 to obtain metal powder; nickel-plated flake graphite and metal powder are mixed in a mass ratio of 0.2:9.8, and mixed and stirred at 30 rpm / min for 5 hours to obtain mixed powder; the particle size of pure copper powder, pure nickel powder and pure titanium powder are all 200 mesh.
[0071] S3. Hot-press the mixed powder and sinter it. Pump the sintering furnace to vacuum. The hot-pressing temperature is 800°C, the heating rate is 50°C / min, the temperature is kept for 0.5 hours, and the pressure is 20MPa. After cooling and demoulding with the furnace, a self-lubricating mold guide plate is obtained.
[0072] Comparative Example 3
[0073] A method for preparing a self-lubricating mold guide plate comprises the following steps:
[0074] S1. Treat 200-mesh flake graphite with microwaves at 20 KW for 3 min to obtain microwave-treated flake graphite.
[0075] S2, placing the microwave-treated flake graphite in plating solution A and stirring evenly, then pouring into plating solution B and stirring evenly, reacting at 55°C for 20 minutes, then washing, filtering and drying to obtain nickel-plated flake graphite; wherein the mass volume ratio of flake graphite, plating solution A and plating solution B is 1kg:5L:5L;
[0076] In plating solution A, the mass ratio of NiSO4, Na3C6H5O7, NaH2PO2 and water is 3:3.5:3.5:100;
[0077] In plating solution B, the mass ratio of NaOH, NH4Cl and water is 0.2:10:100.
[0078] S3. Pure copper powder, pure nickel powder and pure titanium powder are mixed in a mass ratio of 85:10:5 to obtain metal powder; nickel-plated flake graphite and metal powder are mixed in a mass ratio of 0.2:9.8, and mixed and stirred at 30 rpm / min for 5 hours to obtain mixed powder; the particle size of pure copper powder, pure nickel powder and pure titanium powder are all 200 mesh.
[0079] S4. Hot-press the mixed powder and sinter it. Pump the sintering furnace to vacuum. The hot-pressing temperature is 800°C, the heating rate is 50°C / min, the temperature is kept for 0.5 hours, and the pressure is 20MPa. After cooling and demoulding with the furnace, a self-lubricating mold guide plate is obtained.
[0080] Comparative Example 4
[0081] A method for preparing a self-lubricating mold guide plate comprises the following steps:
[0082] S1. Treat 200-mesh flake graphite with a microwave at 20 KW for 20 min to obtain microwave-treated flake graphite.
[0083] S2, placing the microwave-treated flake graphite in plating solution A and stirring evenly, then pouring into plating solution B and stirring evenly, reacting at 55°C for 20 minutes, then washing, filtering and drying to obtain nickel-plated flake graphite; wherein the mass volume ratio of flake graphite, plating solution A and plating solution B is 1kg:5L:5L;
[0084] In plating solution A, the mass ratio of NiSO4, Na3C6H5O7, NaH2PO2 and water is 3:3.5:3.5:100;
[0085] In plating solution B, the mass ratio of NaOH, NH4Cl and water is 0.2:10:100.
[0086] S3. Pure copper powder, pure nickel powder and pure titanium powder are mixed in a mass ratio of 85:10:5 to obtain metal powder; nickel-plated flake graphite and metal powder are mixed in a mass ratio of 0.2:9.8, and mixed and stirred at 30 rpm / min for 5 hours to obtain mixed powder; the particle size of pure copper powder, pure nickel powder and pure titanium powder are all 200 mesh.
[0087] S4. Hot-press the mixed powder and sinter it. Pump the sintering furnace to vacuum. The hot-pressing temperature is 800°C, the heating rate is 50°C / min, the temperature is kept for 0.5 hours, and the pressure is 20MPa. After cooling and demoulding with the furnace, a self-lubricating mold guide plate is obtained.
[0088] In order to further illustrate the performance of the self-lubricating die guide plate of the present invention, an experiment was conducted.
[0089] The self-lubricating die guide plates prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were impacted 100 times with a load of 20 MPa, and the roughness results were calculated as shown in Table 1. The graphite phase peeling of the self-lubricating die guide plate in Example 1 was laser scanned, and the results were as shown in Table 1. Figure 2 shown.
[0090] Table 1 Roughness of guide plates of different lubricating dies
[0091] Group Roughness Comparative Example 1 1.52μm Comparative Example 2 5.58μm Comparative Example 3 1.21μm Comparative Example 4 0.95μm Example 1 0.72μm Example 2 0.58μm Example 3 0.41μm
[0092] It can be seen from the results in Table 1 that the roughness in Examples 1 to 3 is much lower than that in Control Groups 1 to 4. It can be seen from the results of Control Groups 1 to 4 that microwave treatment has the greatest impact on the roughness of the self-lubricating mold guide plate. A microwave treatment time that is too long or too short will affect the roughness of the self-lubricating mold guide plate, thereby increasing its roughness, affecting the interface strength between the graphite phase and the metal, and causing the graphite phase to fall off. In addition, it can be seen from the roughness of Comparative Example 1 that the present invention can further reduce the roughness by introducing nickel powder and titanium powder into the metal powder. This is because the introduction of nickel powder and titanium powder at the same time on the basis of copper powder can form Ni3Ti at the interface of the organization, further improve the interface bonding strength and mechanical properties, ensure the service performance and service life of the mold guide plate, and make it meet the requirements of future high-precision molds for the performance of the guide plate.
[0093] from Figure 2 It can be seen that after the self-lubricating mold guide plate in Example 1 of the present invention was impacted 100 times under a load of 20 MPa, its surface roughness was low and there was no peeling defect, indicating that the method of the present invention can effectively improve the interface strength between the graphite phase and the metal powder, and effectively prevent the problem of graphite phase falling off under a large load, thereby ensuring the service performance and service life of the self-lubricating mold guide plate, so as to meet the requirements of future high-precision molds for guide plate performance.
[0094] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a self-lubricating mold guide plate, characterized in that: The following steps are involved: The flake graphite is subjected to microwave treatment at 20KW to 30KW for 5min to 15min to open the π bond of the flake graphite, and the microwave-treated flake graphite is subjected to nickel plating to obtain nickel-plated flake graphite; Nickel-plated flake graphite and metal powder are mixed in a mass ratio of 0.2-0.8:8-10 to obtain mixed powder, and the mixed powder is hot-pressed and sintered, and cooled to obtain a self-lubricating mold guide plate.
2. The method for preparing the self-lubricating mold guide plate according to claim 1, characterized in that: The specific process of the nickel plating process is as follows: The microwave-treated flake graphite is placed in plating solution A, and then plating solution B is added, reacted at 55° C. to 80° C. for 20 min to 40 min, washed, filtered, and dried to obtain nickel-plated flake graphite; In the plating solution A, the mass ratio of NiSO4, Na3C6H5O7, NaH2PO2 and water is 3.5-4:2.5-3.5:2.5-3.5:100; In the plating solution B, the mass ratio of NaOH, NH4Cl and water is 0.2-0.5:10-15:
100.
3. The method for preparing the self-lubricating mold guide plate according to claim 2, characterized in that: The mass volume ratio of the flake graphite, the plating solution A and the plating solution B is 1kg:5L-6L:5L-6L.
4. The method for preparing the self-lubricating mold guide plate according to claim 1, characterized in that: The particle size of flake graphite is 200 mesh to 325 mesh.
5. The method for preparing the self-lubricating mold guide plate according to claim 1, characterized in that: The metal powder is obtained by mixing copper powder, nickel powder and titanium powder in a mass ratio of 80-85:8-10:2-5.
6. The method for preparing the self-lubricating mold guide plate according to claim 1, characterized in that: The specific process of hot pressing sintering is as follows: The mixed powder is heated to 800°C to 900°C at a heating rate of 50°C / min to 100°C / min under a vacuum condition of 20MPa to 30MPa, and kept at this temperature for 0.5h to 1h.
7. The method for preparing a self-lubricating mold guide plate according to claim 1, characterized in that: The mixing stirring speed is 30 rpm / min to 100 rpm / min, and the mixing time is 5 h to 10 h.
8. A self-lubricating mold guide plate prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Plywood with electromagnetic compatibility and manufacturing method thereof
CN105599392A
Preparation method for nickel element-modified copper-based graphite self-lubricating die guide plate
CN109807332A
Carbon material for nonaqueous secondary battery, negative electrode for nonaqueous secondary battery and nonaqueous secondary battery
JP2012084520A
Quantum teleportation network using a system of electronically enabled graphene waveguides
US20230037977A1